DEVELOPMENT OF INTEGRATED SCIENCE E-MODULES PROBLEMS BASED ON WORK MATERIALS AND ENERGY TO IMPROVE STUDENT LEARNING OUTCOMES - Sarlotha; Samosir, Hotlan; Lumbu , Albert (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2024)
This research aims to find out how to create a problem-based Integrated Science e-module, develop a problem-based Integrated Science e-module, the feasibility of a problem-based Integrated Science e-module, improve learning outcomes for class VIII students using the Science e-module Integrated problem-based material on business and energy. The research method used is research and development (R and D). This research was carried out in class VIII of Yembun State Middle School, Tambrauw Regency with a sample size of 28 students. The research data collection instruments were eligibility validator sheets for lecturers, science teacher response sheets, student response sheets, and pretest and posttest question sheets. The research results show: 1) Making a science e-module with 8 stages. 2) Development of a science e-module through a structure for creating a science e-module in five stages using the ADDIE development model. 3) The feasibility of the science e-module being developed obtained a percentage of 95.26% with the category very suitable for use as teaching material. 4) Integrated Science E-module can improve students' science learning outcomes by obtaining an average n-Gain score of 0.71 in the high category